The Effect of Hydrothermal Treatment on the Biological Properties of Anting-Anting (Acalypha indica Linn.) Plant Extract Containing Carbon Dots - Setiawaty, Natasya Nadia Poetri; Putro, Jindrayani Nyoo; Santoso, Shella Permatasari (Widya Teknik, 2023)
Anting-anting plant (Acalypha indica Linn.) is shrubs that grow as a weed in most parts of tropical countries. The plant has a record of ethno-pharmacological uses by native Asians, the plant has especially been used widely in the therapeutically practice in India. Owing to its rich biological active compounds content, Acalypha indica is rendered as a wild-plants with excellent antioxidant activities. In this work, hydrothermal extraction was performed to obtained liquid products containing high biological active compounds and carbon dots from Acalypha indica plant powder. The effect of hydrothermal temperature of 100, 110, 120, 130, and 140°C was evaluated on the optical properties and biological activity of the resultant liquid products from A. indica. The results imply that the liquid products obtained at highest investigated hydrothermal temperature of 140°C  had the highest total phenolic and total flavonoid content, specifically the calculated total phenolic content is 5.50 mg GAE/g and total flavonoid content is 0.53 mg QE/g; that is higher than the non-hydrothermally treated extract. Owing to the high biological active compounds, the liquid products also show high radical scavenging activity, that is 78.5% against DPPH and 47.2% against superoxide radicals. The antibacterial assays show that the liquid product obtained from hydrothermal treatment at 140°C has better activity than the extract, with inhibition rate of 61.1 and 97.2% against Escherichia coli and Staphylococcus aureus, respectively.